Baudrillard’s Philosophy ofSimulacrum and Religion in "The Grand Inquisitor" from Dostoevsky’s "The Brothers Karamazov:" A sociological analysis of ritual change - Hasan Mousa, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
This paper is concerned with the illustration of the Simulacra, a philosophical concept that was coined by Jean Baudrillard (1929-2007) in his critical essay Simulacra and Simulation (1981). Baudrillard claims that our present society has supplanted all reality and importance with images and signs and that human experience is a simulation that means reproduction of the real world. The study aims to prove the idea of Simulacrum was localized in The Grand Inquisitor (a poetic poem was narrated by Ivan to his brother Alyosha in book V of Fyodor Dostoevsky’s The Brothers Karamazov). It proceeds with the hypothesis that The Grand Inquisitor responds to Jean Baudrillard’s theory of simulacrums, both Baudrillard and Dostoevsky looking to religion under the sign of simulacra. The study is rounded up with concluding verdicts.